Inflammasome components ASC and AIM2 modulate the acute phase of biomaterial implant-induced foreign body responses - Christo, Susan N. (Sci Rep, 2016)
Detailing the inflammatory mechanisms of biomaterial-implant induced foreign body responses (FBR) has implications for revealing targetable pathways that may reduce leukocyte activation and fibrotic encapsulation of the implant. We have adapted a model of poly(methylmethacrylate) (PMMA) bead injection to perform an assessment of the mechanistic role of the ASC-dependent inflammasome in this process. We first demonstrate that ASC(−/−) mice subjected to PMMA bead injections had reduced cell infiltration and altered collagen deposition, suggesting a role for the inflammasome in the FBR. We next investigated the NLRP3 and AIM2 sensors because of their known contributions in recognising damaged and apoptotic cells. We found that NLRP3 was dispensable for the fibrotic encapsulation; however AIM2 expression influenced leukocyte infiltration and controlled collagen deposition, suggesting a previously unexplored link between AIM2 and biomaterial-induced FBR.